X-radiation does not affect the dental pulp: a morphological study in rats - Rafaela Argento; Isadora Luana Flores; Grazielle Oliveira Stelter; Thiago Oliveira Gamba; Solange Maria de Almeida Boscolo; Gláucia Maria Bovi Ambrosano (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2021)
Introduction: Radiotherapy is one of the methods used as a treatment for ma-lignant tumors in the head and neck region and it can cause tissue damage in the irradiated areas. In head and neck radiotherapy, teeth are often included within the irradiation area and, consequently, the dental pulp; which receives high doses of radiation. Objective: To evaluate the effects of ionizing radiation on the pulp tissue of rat teeth. Methodology: A double-blind experimental as-say with 35 Albinus Wistar rats divided into seven groups was performed; one control group, three groups irradiated with 15 Gy, and three groups irradiated with 25 Gy. The irradiated groups were submitted to a single dose of radiation and sacrificed 24 hours, 7 days, and 22 days after irradiation, respectively. The samples were evaluated for the morphological presence of inflammatory infil-trate, edema, necrosis, fibrosis, and degeneration of blood vessels. Statistical analysis was performed using the Kruskal-Wallis and Dunn tests with p